Pembinaan Ekonomi Kreatif Desa Wisata Tanjung Lanjut Dengan Mempertahankan Kearifan Lokal Melalui Badan Usaha Milik Desa - Zulgani; Faradina Zevaya; Etik Umiyati; Helen Parkhurst; Rahma Nurjanah (WIDA Publishing, 2023)
The village of Tanjung Lanjut possesses abundant natural resources and scenic beauty that are yet to be fully explored by external visitors. These potential assets include Lake Tangkas, where hanging trees, putat leaves, and the local tradition of